TECHNOLOGY AND LEARNING: NEW TIMES, NEW TEACHERS: MATHEMATICS TEACHING MEDIATED BY PROJECTS, THROUGH SURVEYING STUDENTS’ INTERESTS - dos Santos, André Gomes; Schimiguel, Juliano (Seven Editora, 2025)
This book chapter addresses the revitalization of mathematics education in the face of contemporary demands, exploring Technology-Mediated Project-Based Learning (PBL) guided by student interests as a transformative pedagogical approach. It analyzes the importance of active methodologies that engage students in the learning process, connecting mathematics to real and meaningful contexts. The chapter discusses how surveying student interests can serve as a starting point for the development of authentic and motivating projects, in which technology acts as an essential tool for research, collaboration, data analysis, and communication of results. It examines the theoretical foundations of PBL and its relevance to mathematics education, presents practical strategies for the implementation of this approach, addresses the challenges, and offers final considerations on the potential of technology-mediated PBL to develop critical, creative, and proficient students in mathematics. DOI: https://doi.org/10.56238/sevened2025.021-064